Fluvial deposits as an archive of early human activity: Progress during the 20 years of the Fluvial Archives Group - Chauhan, Parth R. (2017)
Fluvial sedimentary archives are important repositories for Lower and Middle Palaeolithic artefacts throughout the ‘Old World’, especially in Europe, where the beginning of their study coincided with the realisation that early humans were of great antiquity. Now that many river terrace sequences can be reliably dated and correlated with the globally valid marine isotope record, potentially useful patterns can be recognized in the distribution of the find-spots of the artefacts that constitute the large collections that were assembled during the years of manual gravel extraction. This paper reviews the advances during the past two decades in knowledge of hominin occupation based on artefact occurrences in fluvial contexts, in Europe, Asia and Africa. As such it is an update of a comparable review in 2007, at the end of IGCP Project no. 449, which had instigated the compilation of fluvial records from around the world during 2000e2004, under the auspices of the Fluvial Archives Group. An overarching finding is the confirmation of the well-established view that in Europe there is a demarcation between handaxe making in the west and flakeecore industries in the east, although on a wider scale that pattern is undermined by the increased numbers of Lower Palaeolithic bifaces now recognized in East Asia. It is also apparent that, although it seems to have appeared at different places and at different times in the later Lower Palaeolithic, the arrival of Levallois technology as a global phenomenon was similarly timed across the area occupied by Middle Pleistocene hominins, at around 0.3 Ma.